Agency and structure : dialectics in the administration of education - Watkins, Peter E. (Peter Edwin), 1939- (Administrative context of schooling, 1985)
Produced for unit ESA844 (Administrative context of schooling) offered by the School of Education in Deakin Deakin University's Open Campus Program.